AGRO-CLIMATIC MOISTURE SUPPLY ESTIMATION OF WINTER WHEAT VEGETATION PERIOD IN VINNYTSIA REGION - Kyrnasivska, N. V.; Kolesnikova, O. A. (Scientific Progress & Innovations, 2021)
Soil moisture is a resource for plant growth and development and the main factor that det ermines the conditions of crop existence and tillage. Comparing moisture requirements of plants with the actual water consumption (due to the difference or ratio) can serve as an agro-climatic indicator of moisture supply of the area for growing crops. The article presents the results of agro-climatic estimation of moisture supply of winter wheat crops in Vinnytsia region. To perform the task, the average long-term observation data on the network of meteorological and agro-meteorological stations of the region were analyzed, as well as the annual observation data on the phases of winter wheat, growth and development and productive moisture reserves in the arable (0–20 cm) and meter (0–100 cm) soil layers during the period from 2010 to 2020. The estimation of the correlation between soil moisture and partial field water-holding capacity for the main phases of winter wheat development in 0-50, 0-100 cm soil layers allowed to establish that for the phase of vegetation restoration in the soil layer of 0-50 cm, the deficit of soil moisture was insignificant and did not exceed 28 mm on the territory of the region. The reserves of productive moisture in the soil layer of 0- 100 cm on the date of earing of winter wheat made 53-74 % of partial field water-holding capacity. For agro-climatic areas of the region, the average long-term characteristics of moistening conditions for the period of winter wheat active vegetation were analyzed. Based on the average long-term conditions of the water regime in the growing season of winter wheat, the actual moisture supply of winter wheat crops in the first agro-climatic region amounted to 92-100 %, and in the second agro-climatic region – 65-84 %. The analysis of annual productive moisture reserves in the soil arable layer has shown the greatest variability of moisture supply in the autumn period, which is associated with changes in the precipitation regime. For the first time for the territory of Vinnytsia region, the supply of productive moisture resources in the soil before the beginning of the main phases of winter wheat development by gradations, designated 10 mm in the arable layer on the date of sowing, and 25 mm in the meter layer of soil on the date of vegetation, earing and wax ripeness, was determined.